The ‘Feudal Revolution’ and the origins of italian city communes - Wickham, C (Cambridge University Press, 2014)
This article takes two major moments of social change in central medieval Europe, the ‘feudal revolution’ in France and the origins of Italian city communes, in order to see what they have in common. They are superficially very different, one rural one urban, and also one whose analysts focus on the breakdown of political power and the other on its construction or reconstruction; but there are close parallels between the changes which took place in France around 1000 or 1050 and those which took place in Italy around 1100. The contrast in dates does not matter; what matters is that in each case larger-scale political breakdown (whether at the level of the kingdom or the county) was matched by local recomposition, the intensification or crystallisation of local power structures which had been much more ad hoc before, and which would be the basic template for local power henceforth. In Italy, the main focus of the article, the different experiences of Pisa and Genoa are compared, and the development of urban assemblies first, consular collectives second, communal institutions third, are all analysed from this perspective, as guides to how the city communes of the peninsula developed, however haltingly and insecurely. The article finishes with a brief comment on the sociology of Pierre Bourdieu.